Castration and the heavenly kingdom : a Russian folktale - Engelstein, Laura (Cornell University Press, 1999)
"Of the many sects that broke from the official Russian Orthodox church in the eighteenth century, one was universally despised. Its members were peasants from the Russian heartland skilled in the arts of animal husbandry who turned their knives on themselves to become "eunuchs for the kingdom of heaven's sake."" "In a feat of historical reconstruction, Laura Engelstein tells the sect's astonishing tale. She describes the horrified reactions to the sect by outsiders, including outraged bureaucrats, physicians, and theologians. More important, she allows the Skoptsy a say in defining the contours of their history and the meaning behind their sacrifice."--Jacket